A abordagem do léxico no ensino de língua inglesa: relações semântico-lexicais em materiais didáticos - Barbosa, Tatiana Ramalho (2023)
Studies related to the lexicon have played a significant role in understanding linguistic phenomena that help in language teaching. Through the investigation of vocabulary, it has been possible to advance in the elaboration of materials that introduce the student to the understanding that the study of semantic-lexical relations is of great use in language learning. Furthermore, obtaining proficiency, especially in English, also requires taking into consideration: chunks, phrasal verbs and collocations, since it is through these lexical items that new meanings and senses are created. It is also known that, although the English language is commonly offered in Brazilian schools, teaching often focuses only on reading, neglecting writing and speaking. Furthermore, when dealing with language aspects, it usually focuses on grammatical issues, neglecting the study of the lexicon. As a result, many students finish high school without basic knowledge of the English language. In this context, this research aims to investigate the place of lexicon in materials in English Language Teaching (ELT). Based on the principles of the Lexical Approach (Lewis, 1993) and with the support of Lexical Semantics (Ferraz, 2013; Ferraz; Nascimento, 2015; Antunes, 2012). It is, therefore, a documental, qualitative and interpretive research. After a first stage of construction of the theoretical framework and discussion of the official documents, an analysis of a textbook for the 3rd Grade of high school education, produced by Editora Somos, is carried out. Approaches related to lexicon teaching are analyzed in order to verify how new vocabulary is presented and explored in this material. It is observed that there is a concern to present a large number of texts, however, in an isolated way, including, mostly, lists of words with definitions and general questions of textual interpretation, which is not considered the most suitable strategy, especially for the teaching segment in which the material is used. Finally, at the conclusion of this research, a pedagogical notebook containing complementary activities is presented, in the light of lexical semantics, so that the lexicon is taught in a more effective and contextualized way, promoting greater proficiency of the students.